Associations of PGK1 promoter hypomethylation and PGK1‐mediated PDHK1 phosphorylation with cancer stage and prognosis: a TCGA pan‐cancer analysis. Issue 1 (2nd October 2019) - Shao, Fei; Yang, Xueying; Wang, Wei; Wang, Juhong; Guo, Wei; Feng, Xiaoli; Shi, Susheng; Xue, Qi; Gao, Shugeng; Gao, Yibo; Lu, Zhimin; He, Jie
Abstract: Background: Cancer cells reprogram metabolism for proliferation. Phosphoglycerate kinase 1 (PGK1), as a glycolytic enzyme and newly identified protein kinase, coordinates glycolysis and mitochondrial metabolism. However, the clinical significance of PGK1 expression and function in cancer progression is unclear. Here, we investigated the relationship between the progression and prognosis of multiple cancer types and PGK1 expression and its function in the mitochondrial metabolism regulation. Methods: We performed pan‐cancer analyses of PGK1 mRNA level and DNA methylation in 11, 908 tumor tissues and 1582 paired normal tissues across 34 cancer types in The Cancer Genome Atlas datasets. Using specific antibodies against PGK1 S203 and PDHK1 T338 phosphorylation, we performed immunohistochemistry with tissue microarray assay in additional 818 cancer cases with 619 paired normal tissues from five cancer types. Results: The PGK1 mRNA level was significantly elevated with hypomethylation in promotor regions and associated with advanced TNM stage in 15 and four cancer types, respectively. In breast carcinoma, elevated PGK1 mRNA level and promoter hypomethylation were associated with poor prognosis. Positively correlated PGK1 S203 and PDHK1 T338 phosphorylation levels were significantly associated with short overall survival (OS) in cancers of the breast, liver, lung, stomach, and esophagus and with advanced TNM stage in breast and esophageal cancers. PGK1 pS203 and PDHK1 pT338 were also independent predictors of short OS in liver, lung, and stomach cancer. Conclusions: The elevated expression, promoter hypomethylation, and phosphorylation of PGK1 and PDHK1 were related with disease progression and short OS in diverse types of cancer. PGK1 and PDHK1 phosphorylation may be potential prognostic biomarkers.